A tandem approach for the synthesis of 1-phenyl-pyrazolo-quinolinones by Fe3O4@MWCNT nanocomposite as heterogeneous catalyst - Adapaka Venkateswara Rao; Suresh Maddila; Nagaraju Kerru; Sreekantha B. Jonnalagadda (Green Chemistry Letters and Reviews)
A simple, facile, efficient and highly promising protocol for the synthesis of 1-phenyl-pyrazolo-quinolinone analogs using Fe3O4@MWCNT nano-composite as a catalyst via Knoevenagel–Michael reaction has been developed. The use of Fe3O4@MWCNT nano-composite as a catalyst has several advantages, like simple preparation, inexpensive, simple handling, and high stability. It was synthesized from MWCNT and iron oxide and was thoroughly characterized using BET, PXRD, SEM, TEM, and TGA analysis. All the synthesized target molecules were characterized and confirmed by various spectroscopic techniques such as 1H-NMR, 15N-NMR, 13C-NMR, and HRMS. The present work unveils a promising and environmentally friendly approach for synthesizing phenyl-pyrazolo-quinolinone scaffolds with higher yields (93–97%), selectivity, efficiency, using mild reaction conditions, no need for chromatographic separation, short reaction times, catalyst recovery and reuse for a minimum of seven cycles is possible without causing a notable reduction in product yields. The method complies with green chemistry principles and presents a feasible alternative to previously documented techniques.